The Study of Waste Management and Its Usefulness in the Old City Area, Jakarta - Pramiati Purwaningrum; Dwi Indrawati; Tasya Oemar; Grace Celine Simatupang (Fakultas Teknik, 2022)
The Old City is an area with high economic value because they have different tourist centers, businesses, services, and trades. However, the residents' settlements and other activities in this area failed to be equipped with adequate sanitation facilities. In DKI Jakarta, rapid population growth directly and indirectly affects waste volume generation because waste management needs to be properly performed in line with existing regulations. This situation makes it necessary for people to discover the recyclable and processing organic waste. The results showed that the waste generation rate in Taman Sari Sub-District was 2.75 liters/person/day. It also indicated that organic, plastic, and paper waste are 29.24%, 35.09%, and 27.13% respectively. Therefore, organic waste processing needs to be performed by composting using the Black Soldier Fly larvae media such as magot.